Safety and rate of delayed adverse events with lumen-apposing metal stents (LAMS) for pancreatic fluid collections: a multicenter study - Yang, Dennis; Perbtani, Yaseen B.; Mramba, Lazarus K; Kerdsirichairat, Tossapol; Prabhu, Anoop; Manvar, Amar; Ho, Sammy; Pannu, Davindebir; Keswani, Rajesh N.; Strand, Daniel S.; Wang, Andrew Y.; Quintero, Eduardo; Buscaglia, Jonathan M.; Muniraj, Thiruvengadam; Aslanian, Harry R.; Draganov, Peter V.; Siddiqui, Ali S. (Endoscopy International Open, 2018)
Background and study aims Endoscopic drainage with dedicated lumen-apposing metal stents (LAMS) is routinely performed for symptomatic pancreatic fluid collections (PFCs), walled-off necrosis (WON) and pseudocyst (PP). There has been increasing concern regarding delayed adverse events associated with the indwelling LAMS. Patients and methods Multicenter retrospective analysis of consecutive patients who underwent endoscopic ultrasound (EUS)-guided LAMS placement for PFC from January 2010 to May 2017. Main outcomes included: (1) resolution of the PFC, (2) rate of delayed adverse events at follow-up, and (3) predictors of treatment failure and delayed adverse events on logistic regression. Results A total of 122 patients (mean age 50.9 years, 68 % male) underwent LAMS insertion for 64 WON (98.4 %) and 58 PP (98.3 %). PFC mean size was 10.6 cm. PFC resolution was significantly lower for WON (62.3 %) vs. PP (96.5 %) (P < 0.001) on imaging at a median of 4 weeks. Stent occlusion was identified in 18 (29.5 %) and 10 (17.5 %) patients with WON and PP, respectively (P = 0.13). There were no cases of delayed bleeding or buried stent on follow-up endoscopy. Use of electrocautery-enhanced LAMS was the only factor associated with treatment failure of WON (OR = 13.2; 95 % ci: 3.33 – 51.82, P = 0.02) on logistic regression. There were no patient, operator, or procedure-related factors predictive of stent occlusion.Conclusions EUS-guided LAMS for PFC is associated with a low incidence of delayed adverse events. While nearly all PPs resolve at 4 weeks permitting LAMS removal shortly thereafter, many WON persist, with use of electrocautery-enhanced LAMS being the sole predictor of treatment failure.